Solve the flowing pair of linear equations by the substituting method 3x-y=3
9x-3y=9
Answers
Solving the equations by using substitution method..
3x - y = 3. (1)
9x - 3y = 9 (2)
3x - y = 3
- y = 3 - 3x (3)
Put the value of (3) in (2) equation .
9x - 3y = 9
9x - 3 ( 3 - 3x ) = 9
9x - 9 + 9x = 9
9x + 9x = 9 + 9
18x = 18
x = 1..
Now put the value of x in (3) equation..
- y = 3 - 3x
- y = 3 - 3 ( 1 )
- y = 3 - 3
- y = 0...
I hope it help you...
If you like my answer then Plz mark it as a brainliest answer....
^_^ >° _ °<
HERE IS YOUR ANSWER MATE.....;
(i) Given,
x + y = 14 and x – y = 4 are the two equations.
From 1st equation, we get,
x = 14 – y
Now, put the value of x in second equation to get,
(14 – y) – y = 4
14 – 2y = 4
2y = 10
Or y = 5
By the value of y, we can now find the value of x;
∵ x = 14 – y
∴ x = 14 – 5
Or x = 9
Hence, x = 9 and y = 5.
(ii) Given,
3x – y = 3 and 9x – 3y = 9 are the two equations.
From 1st equation, we get,
x = (3 + y)/3
Now, substitute the value of x in the given second equation to get,
9[(3 + y)/3] – 3y = 9
⇒ 3(3+y) – 3y = 9
⇒ 9 + 3y – 3y = 9
⇒ 9 = 9